Penerjemahan Satuan-Satuan Budaya dalam Cerpen Powder Karya Tobias Wolff Ke dalam Bahasa Indonesia - Doni Jaya; Ismirani Mardalena (Ranah: Jurnal Kajian Bahasa, 2026)
This study aims to identify the translation strategies of cultural items in Tobias Wolff’s short story Powder used by a team of student-translators to produce its Indonesian translation. Data consist of pairs of English source texts (ST) and Indonesian target texts (TT) in the form of words, phrases, and expressions with specific cultural content. which were collected and categorized according to Newmark’s cultural words classification Next, the translation strategy of each unit of analysis was identified according Dewi and Wijaya’s translation procedures. Results show that those cultural items can be classified into five categories: popular culture, cultural objects, cultural concepts, individuals, and expressions. The translators used various strategies, such as cultural equivalent, descriptive equivalent, transference, and contextual conditioning to preserve meaning and facilitate understanding. This study shows that translation of cultural items is a balancing act between preserving the source text’s cultural nuances and the target text’s acceptability in the target culture. Findings are expected to contribute to the areas of literary and cultural item translation. Abstrak Penelitian ini bertujuan untuk menemukan strategi penerjemahan yang digunakan dalam penerjemahan satuan budaya yang muncul dalam cerpen Powder karya Tobias Wolff ke dalam bahasa Indonesia. Data penelitian berupa pasangan teks sumber (TSu) berbahasa Inggris dan teks sasaran (TSa) berbahasa Indonesia dalam bentuk kata, frasa, dan ungkapan yang mengandung unsur budaya dikumpulkan dan dibagi berdasarkan klasifikasi unsur budaya Newmark. Lalu, strategi penerjemahan setiap satuan analisis ditentukan menurut teori Dewi dan Wijaya. Hasil penelitian menunjukkan bahwa satuan budaya dalam cerpen itu dapat dibagi ke dalam lima kategori, yaitu budaya populer, benda budaya, konsep budaya, orang, dan ungkapan. Dalam proses penerjemahan, penerjemah menggunakan berbagai strategi, antara lain padanan budaya, padanan deskriptif, transferensi, serta pemadanan berkonteks, untuk mempertahankan makna dan memudahkan pemahaman pembaca sasaran. Penelitian ini menunjukkan bahwa penerjemahan satuan budaya memerlukan keseimbangan antara mempertahankan warna budaya sumber dan keberterimaan teks dalam budaya sasaran. Hasil penelitian diharapkan dapat memberikan kontribusi bagi kajian penerjemahan sastra dan penerjemahan unsur budaya.